Pengaruh Pengalaman Auditor, Komitmen Organisasi, Kompetensi Auditor dan Reward Pada Audit Judgment - Krisdhayani, Ni Made; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 25 No 3 (2018)DO - 10.24843/EJA.2018.v25.i03.p03, 2018)
The purpose of this study was to obtain empirical evidence of the influence of auditor experience, organizational commitment, auditor competence and reward on audit judgment in KAP Bali Province. This research was conducted at the Public Accountant Office in Bali Province. The population of this study is all auditors working in the Public Accountants Office in Bali in 2017, amounting to 77 people. The unit of analysis of this study is the individual who is the auditor who works in 9 Public Accounting Firms in Bali Province. The sample determination technique used in this study is saturated sample or census technique, which is the technique of determining samples with all members of the population used as samples. The data analysis technique used in this study is multiple linear regression analysis. The results of the analysis show that auditor experience has a positive effect on audit judgment, organizational commitment has a positive effect on audit judgment, auditor competence has a positive effect on audit judgment, and reward has a positive effect on audit judgment. Keywords: experience, commitment, competence, reward, audit judgment